Expanding Florida's Farming Business to Incorporate Tourism - Wendy Francesconi; Taylor V. Stein (EDIS)
FOR-187, a 5-page fact sheet by Wendy Francesconi and Taylor Stein, proposes bringing Florida’s two economic engines, tourism and agriculture, together. Describes the current farming situation in Florida, why Florida farmers should consider agritourism, and planning needed for an agritourism operation. Includes references. Published by the UF School of Forest Resources and Conservation, June 2008.